A change in response to Bmp signalling precedes ectodermal fate choice. - Dee, C; Gibson, A; Rengifo, A; Sun, S; Patient, R; Scotting, P (2007)
Bone morphogenetic protein (Bmp) signalling plays a central role in the decision of ectoderm to adopt either neural or non-neural fates. The effects of this signalling are seen at mid-gastrulation in the activation of genes such as the Gata factors and the repression of genes such as the SoxB1 transcription factors in the non-neural regions. Using zebrafish embryos, we show that this Bmp signalling does not repress the expression of these same neural markers just 2-3 hours earlier. Since expression of the Bmp signalling effector, Smad1, only begins during early gastrulation, we tested the role of Smad1 and Smad5 (which is maternally expressed) in controlling gene expression both before and during gastrulation. This showed that the absence of Smad1 does not explain the lack of response of neural genes to Bmp signalling at early stages. However, these experiments showed that expression of the non-neural marker, gata2, is mediated by Smad5 in the absence of Smad1 at early stages, but is dependent upon Smad1 at later stages. Hence, we have shown a dynamic change in the molecular machinery underlying the Bmp response in the ectoderm during gastrulation stages of development.